Peer relationship antecedents of delinquent behavior in late adolescence: Is there evidence of demographic group differences in developmental processes? - LAIRD, ROBERT D. (2005)
A longitudinal prospective design was used to test the generalizability of low levels of social preference and high levels of antisocial peer involvement as risk factors for delinquent behavior problems to African American (AA) and European American (EA) boys and girls (N = 384). Social preference scores were computed from peer reports in middle childhood (ages 6–9). Parents and adolescents reported antisocial peer involvement in early adolescence (ages 13–16) and adolescents reported on their own delinquent behavior in late adolescence (ages 17 and 18). Analyses tested for differences across four groups (AA boys, EA boys, AA girls, EA girls) in construct measurement, mean levels, and associations among variables. Few measurement differences were found. Mean-level differences were found for social preference and delinquent behavior. AA boys were least accepted by peers and reported the highest level of delinquent behavior. EA girls were most accepted by peers and reported the lowest level of delinquent behavior. Associations among peer experiences and delinquent behavior were equivalent across groups, with lower levels of social preference and higher levels of antisocial peer involvement associated with more delinquent behavior. Person-centered analyses showed the risk associated with low social preference and high antisocial peer involvement to be similar across groups, providing further evidence of the generalizability of the peer relationship experiences as risk factors for subsequent delinquent behavior problems.